Walking between slums and skyscrapers : illusions of open space in Hong Kong, Tokyo, and Shanghai - Huang, Tsung-yi Michelle (UPCC book collections on Project MUSE., 2004)
"This book is concerned with the effects of globalization on living space (i.e., the space of everyday life), focusing specifically on East Asian metropolises, such as Hong Kong, Tokyo, and Shanghai. Globalization has given rise to accessible catch-phrases such as the 'global village' and 'this is a small world'. In each part of the book the author juxtaposes a 'social' account of the city's urban space as it has been reshaped by the process of globalization with a 'private' account of the urban landscape as experienced by its walkers (as represented in the films of Wong Kar-wai and Shinya Tsukamoto and the novels of Wang Anyi). Rather than rest here, the author wishes to show that for many of the inhabitants of the new global city, the 'shrinking world' phenomenon is deeply literal : the 'lived' space of everyday life is shrinking to make room for rezoning, construction of new infrastructures, and space modification - all in the name of urban development"--Back cover.